2019
DOI: 10.1016/s1473-3099(18)30685-6
|View full text |Cite
|
Sign up to set email alerts
|

The global burden of typhoid and paratyphoid fevers: a systematic analysis for the Global Burden of Disease Study 2017

Abstract: Summary Background Efforts to quantify the global burden of enteric fever are valuable for understanding the health lost and the large-scale spatial distribution of the disease. We present the estimates of typhoid and paratyphoid fever burden from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017, and the approach taken to produce them. Methods For this systematic analysis we broke down the relative contributions of typhoid and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
409
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(460 citation statements)
references
References 24 publications
8
409
1
8
Order By: Relevance
“…Introduction Salmonella enterica serovar Typhi (S. enterica serovar Typhi or S. Typhi) is a human hostrestricted pathogen that is the cause of typhoid fever affecting 10.9 million people worldwide annually [1]. Following the ingestion of contaminated food or water, S. Typhi invades the intestinal mucosa and spreads systemically to the liver and spleen, which can result in the acute symptoms of typhoid fever.…”
mentioning
confidence: 99%
“…Introduction Salmonella enterica serovar Typhi (S. enterica serovar Typhi or S. Typhi) is a human hostrestricted pathogen that is the cause of typhoid fever affecting 10.9 million people worldwide annually [1]. Following the ingestion of contaminated food or water, S. Typhi invades the intestinal mucosa and spreads systemically to the liver and spleen, which can result in the acute symptoms of typhoid fever.…”
mentioning
confidence: 99%
“…enterica serovar Typhi and S. enterica subsp. enterica serovar Paratyphi A, B, and C. S. Typhi causes approximately 76.3% of global enteric fever cases [78]. S. Typhi and S. Paratyphi are restricted to humans and higher primates, and clinical manifestations of the infection include sustained high fever, abdominal pain, headache, weakness, malaise, and transient diarrhea/constipation.…”
Section: Salmonella Entericamentioning
confidence: 99%
“…NTS causes more than 93 million global infections per year, with 155,000 deaths [85]. A study examining the global burden of diseases, injuries, and risk factors in 2017 reported 14.3 million cases of enteric fever globally, with a case fatality of 0.95% resulting in approximately 135,000 deaths [78]. Children, elderly, and those residing in lower-income countries account for the greatest incidences [86,87].…”
Section: Salmonella Entericamentioning
confidence: 99%
“…Salmonella yang mencemari makanan dan minuman menyebabkan demam tifoid (Raffatellu et al 2008). Diagnosis yang terlambat dan pengobatan yang salah dapat berakibat fatal pada pada penderita demam tifoid karena menyebabkan pendarahan saluran cerna yang mengakibatkan kematian (Stanaway et al 2019;Goay et al 2016). Metode deteksi Salmonella yang diinginkan mempunyai sensitifitas untuk mendeteksi satu sel dalam sampel, cepat, spesifik, dan akurat (Lee et al 2015).…”
Section: Pendahuluanunclassified